2004
DOI: 10.4049/jimmunol.172.4.2316
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-3 Is a Component of Fas Death-Inducing Signaling Complex in Lipid Rafts and Its Activity Is Required for Complete Caspase-8 Activation during Fas-Mediated Cell Death

Abstract: Since its discovery, caspase-8 has been placed at the apex of the proteolytic cascade triggered by death receptor (DR) cross-linking. Because of its capacity to interact with the cytoplasmic portion of DR, it has been suggested that caspase-8 acts independently of other caspases in the initiation of Fas and other DR signaling. In this study, we demonstrate that in Jurkat cells, caspase-3 cleavage is an early step during Fas-induced apoptosis. We show that caspase-3 processing into its p20 occurs rapidly after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
43
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 47 publications
8
43
1
Order By: Relevance
“…Since XIAP does not bind to and directly regulate caspase-8 , the increased levels of active caspase-9 and -3 in the absence of XIAP likely work in a feed forward manner to further process procaspase-8 leading to greater BID cleavage. This hypothesis is in agreement with a recent study demonstrating that caspase-3 is an integral component of the death-inducing signaling complex (DISC) and required for optimal caspase-8 activation (Aouad et al, 2004). Therefore, the loss of XIAP would be expected to enhance caspase-3 processing of caspase-8 in response to TRAIL treatment, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 83%
“…Since XIAP does not bind to and directly regulate caspase-8 , the increased levels of active caspase-9 and -3 in the absence of XIAP likely work in a feed forward manner to further process procaspase-8 leading to greater BID cleavage. This hypothesis is in agreement with a recent study demonstrating that caspase-3 is an integral component of the death-inducing signaling complex (DISC) and required for optimal caspase-8 activation (Aouad et al, 2004). Therefore, the loss of XIAP would be expected to enhance caspase-3 processing of caspase-8 in response to TRAIL treatment, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 83%
“…Rafts are organized membrane domains mainly composed of glycosphingolipids, sphingomyelin, cholesterol and specific membrane proteins (Simons and Ikonen, 1997;Brown and London, 1998). Several studies indicated that rafts are required to cluster CD95 and to recruit FADD, caspase 8 and 3 to CD95 upon stimulation (Grassme et al, 2001bHueber et al, 2002;Scheel-Toellner et al, 2002;Delmas et al, 2003;Aouad et al, 2004;Eramo et al, 2004). Accordingly, disruption of rafts prevented CD95-induced apoptosis, at least in most cells (Grassme et al, 2001b;Cremesti et al, 2001;Hueber et al, 2002;Scheel-Toellner et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol and sphingolipid-enriched rafts, also called detergent-resistant membranes, have been proposed as platforms for compartmentalizing dynamically regulated Fas signaling complexes at the plasma membrane (16, 22, 59 -61). Although detected in various cell types, the role of lipid rafts in apoptosis has, however, been mostly studied in lymphocytes where the physiological apoptotic program occurs after Fas receptor triggering using conventional Triton X-soluble and -insoluble fractions isolated by sucrose gradient (15)(16)(17)(18)(19)(20)(21)(22). The cells stimulated to undergo apoptosis appear to use membrane rafts in the death-signaling process by mobilization of rafts to localized regions of the membrane that are now enriched with apoptotic signaling effectors.…”
Section: Figure 7 Defective Cell Death In Cd4mentioning
confidence: 99%
“…Although the DISC is rapidly assembled, several lines of evidence suggest that formation of this complex is not the first consequence of Fas stimulation but rather a later step in the conversion of signaling "inefficient" Fas complexes into "activated" receptor complexes (11,12). In particular, formation of Fas microclusters (12) and high stability supramolecular clusters via receptor palmitoylation (13, 14), actin reorganization (12), inducible or constitutive association with detergent-resistant microdomains known as lipid rafts (15)(16)(17)(18)(19)(20)(21)(22), and the production of acid sphingomyelinase-mediated ceramide (11) have been proposed as important intermediate steps preceding robust DISC formation.These studies clearly suggest that Fas-induced apoptosis can be controlled at the level of the cytoplasmic membrane. Although specific interactions between Fas, FADD, and procaspase-8/10 via their death domains and death effector domains are well documented, little is known about the mechanism(s) that regulates the recruitment of these proteins to CD95 after anti-Fas treatment.…”
mentioning
confidence: 99%